Konstruktionen mediterraner Insularitäten - Bendemann, Reinhard von; Gerstenberg, Annette; Jaspert, Nikolas; Kolditz, Sebastian; Kelzenberg, Kathrin (Mittelmeerstudien, 2016)
The contributions in this volume are devoted to the concept of "insularity" in the Mediterranean world. The scholarly concept covered by the term "insularity" is closely tied to questions concerning the specific biological, economic, political, military, cultural, and religious phenomena of islands, resulting simply from the fact that islands are completely surrounded by water and are limited in their resources. These simple criteria, however, account for a great diversity of ways of constructing insularity in the Mediterranean world, in both texts and images. The articles in this volume cover a wide chronological range, from the ancient to the medieval. They also cover a wide range of disciplines, including the history of theology, literary criticism, the study of migration, sociology, and the comparative study of islands (nissology)
"Der vorliegende Sammelband dokumentiert die Ergebnisse der vom Bochumer Zentrum für Mittelmeerstudien veranstalteten Tagung "Konstruktionen mediterraner Insularitäten" (31. Mai und 1. Juni 2013)"
Keywords: Mediterranean Region -- Antiquities -- Congresses; Mediterranean Region -- Research -- Congresses; Mediterranean Region -- History -- Congresses; Konferenzschrift; Vorstellung; Insel; Mittelmeer